Analisis Kepuasan Pelanggan terhadap PT.XYZ dengan Menggunakan Metode Recency, Frequency, Monetary (RFM) dan K-Means Clustering - Zamzani, Muhamad Imron; Suryadiningrat, Akmal Almas; Imam Al Kharazi, Alif; Yusuf Alifiar, Muhamad (SURYA TEKNIKA, 2026)
The increasingly intense competition in the fast food industry requires companies to understand customer behavior more accurately so that marketing strategies can be directed effectively. However, PT XYZ has not yet had customer segmentation based on transaction data that can objectively represent customer loyalty and value. This study aims to segment PT XYZ's customers based on transaction behavior using the Recency, Frequency, Monetary (RFM) approach and the K-Means Clustering algorithm. This study uses a descriptive quantitative method with historical transaction data from 200 customers. The results of the study show the formation of four customer segments, namely low value customers, occasional customers, loyal customers, and high value customers, each with different behavioral characteristics. These segmentation results are expected to serve as a basis for the company in formulating more targeted marketing strategies.